School principal's role and perceptions : actual and perceived role of a school principal: a case study - Nasr, Tina F (Beirut Lebanese American University- School of Arts and Sciences - Department of Education., 2005)
The purpose of the present study was to examine the actual role of a school principal and his role as perceived by teachers and students. The sample of this study consisted of 1 principal, 30 teachers and 60 students, all taken from one school in Lebanon. The instruments used were interviews and questionnaires developed according to the Western literature. The results revealed that a school principal should be a manager and a leader simultaneously. The school principal in this study perceived himself to be a problem-solver, a decision-maker, and a vision-builder who is concerned about the students' learning and the teachers' professional development. Similarly, the teachers perceived the school principal as a friendly individual with an open communication system and a cooperative leadership style, who frequently meets the needs of school members. Also, the teachers believed that the academic domain and the students' disciplinary behaviors were the major issues that the principal dealt with. Additionally, the students perceived the school principal as showing concern about their needs. Students also believed that the principal focused mostly on the academic domain in the school. Finally, the students perceived the existence of a friendly relationship between themselves and the principal as well as the continuous availability of the principal at school.
: Mémoire
Keywords: Gestion scolaire; School management